The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/aic.11863
|View full text |Cite
|
Sign up to set email alerts
|

Radiation model of a TiO2‐coated, quartz wool, packed‐bed photocatalytic reactor

Abstract: The radiation field of a packed-bed photocatalytic reactor filled with quartz wool coated with titanium dioxide was modeled using the Monte Carlo technique and the following information: the radiation flux emitted by the lamps, the diameter size distribution of the quartz fiber cloth, the mass of quartz fibers and of TiO 2 that was immobilized on the fiber surface as well as the refractive index, and the spectral absorption coefficient of the materials of the system. Modeling predictions were validated with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…It is thought that insufficient amount of research on photoreactor modeling, and thus a lack of readily applicable mathematical models to reactor design and scale-up, is the reason of impeding application of photocatalytical method for wastewater treatment on an industrial scale [116]. Fortunately, recently large amount of research on modeling different kind of photoreactors has been performed, mainly by the group of Cassano and Alfano [2,112,[121][122][123][124][125][126][127][128][129]. 1 -UV/vis lamp (XeL), 2 -pyrex glass window, 3 -cut-off filter, 4 -filter holder, 5 -separating wall for water circulation, 6 -water inlet, 7 -water outlet, 8 -water bath, 9 -hole for circulating water, 10 -reactor covers, 11 -sample tubes holder, 12 -sample tubes (two), 13 -stirrers (two) [68].…”
Section: Common Name [3] Radiation Source Oxidation System/applicatiomentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that insufficient amount of research on photoreactor modeling, and thus a lack of readily applicable mathematical models to reactor design and scale-up, is the reason of impeding application of photocatalytical method for wastewater treatment on an industrial scale [116]. Fortunately, recently large amount of research on modeling different kind of photoreactors has been performed, mainly by the group of Cassano and Alfano [2,112,[121][122][123][124][125][126][127][128][129]. 1 -UV/vis lamp (XeL), 2 -pyrex glass window, 3 -cut-off filter, 4 -filter holder, 5 -separating wall for water circulation, 6 -water inlet, 7 -water outlet, 8 -water bath, 9 -hole for circulating water, 10 -reactor covers, 11 -sample tubes holder, 12 -sample tubes (two), 13 -stirrers (two) [68].…”
Section: Common Name [3] Radiation Source Oxidation System/applicatiomentioning
confidence: 99%
“…The models concerning emission/absorption of light and reaction run inside a photoreactor have been also examined [2,[110][111][112], e.g. LSSE-LSPP model for laminar falling film slurry (LFFS) photoreactor [110], zero reflectance model (ZRM) and two-flux model (TFM) for the prediction of radiation fields inside heterogeneous photocatalytic reactor [113,114].…”
Section: Common Name [3] Radiation Source Oxidation System/applicatiomentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a significant research effort reported in the technical literature by several research groups to model radiation in photoreactors 41–50. The evaluation of the rate of photons absorbed as shown in Eq.…”
Section: Rates Of Absorbed Photonsmentioning
confidence: 99%
“…Imoberdorf et al [7] proposed a predictive model to solve the radiation transfer equation in a fluidized bed photocatalytic reactor, based on the MC approach coupled with the ray tracing technique. Imoberdorf et al [8] also modeled the radiation field of a packed-bed photocatalytic reactor filled with quartz wool coated with titanium dioxide using the MC technique. Moreira et al [9] used the MC method along with an optimization technique in a Photo-CREC annular photocatalytic reactor to estimate the wavelength-averaged absorption and scattering coefficients for three different TiO2 powders.…”
Section: Introductionmentioning
confidence: 99%